2014
DOI: 10.1175/jtech-d-13-00059.1
|View full text |Cite
|
Sign up to set email alerts
|

Radio Occultation Observations as Anchor Observations in Numerical Weather Prediction Models and Associated Reduction of Bias Corrections in Microwave and Infrared Satellite Observations

Abstract: Satellite radiance measurements are used daily at numerical weather prediction (NWP) centers around the world, providing a significant positive impact on weather forecast skill. Owing to the existence of systematic errors, either in the observations, instruments, and/or forward models, which can be larger than the signal, the use of infrared or microwave radiances in data assimilation systems requires significant bias corrections. As most bias-correction schemes do not correct for biases that exist in the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 36 publications
(31 reference statements)
4
59
0
Order By: Relevance
“…Positive results were confirmed at various meteorological centers (e.g., Healy and Thépaut 2006;Cucurull et al 2007;Aparicio and Deblonde 2008;Rennie 2008). GPSRO probes with high vertical resolution regions that are otherwise poorly sampled, or where most data are of low vertical resolution, most notably over the oceans and polar areas.…”
Section: Introductionmentioning
confidence: 82%
“…Positive results were confirmed at various meteorological centers (e.g., Healy and Thépaut 2006;Cucurull et al 2007;Aparicio and Deblonde 2008;Rennie 2008). GPSRO probes with high vertical resolution regions that are otherwise poorly sampled, or where most data are of low vertical resolution, most notably over the oceans and polar areas.…”
Section: Introductionmentioning
confidence: 82%
“…The cold bias in the NCEP stratospheric analyses and forecasts is well known (Yang 2013). The ability of the unbiased RO observations to reduce or eliminate biases in the stratosphere is also well known (Healy et al 2005;Healy and Thépaut 2006;Healy 2008;Poli et al 2010;Cucurull at al. 2014).…”
Section: A Fit Of Analyses To Radiosondesmentioning
confidence: 99%
“…The role of RO observations as ''anchor observations'' in NWP models and the resulting improvements in the bias correction of the satellite radiances has been shown in a number of studies (Healy et al 2005;Healy and Thépaut 2006;Healy 2008;Poli et al 2010;Bauer et al 2014;Cucurull at al. 2014;Bonavita 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on recent studies, contributions from satellite data, especially data from infrared (IR) and microwave (MW) sounders such as Atmospheric Infrared Sounder (AIRS), Infrared Atmospheric Sounding Interferometer (IASI), Crosstrack Infrared Sounder (CrIS), Advanced Microwave Sounding Unit-A (AMSU-A), AMSU-B, Microwave Humidity Sounder (MHS), etc., are becoming the most important observations in operational centers (Le Marshall et al, 2005Marshall et al, , 2006Kelly and Thepaut, 2007;Cardinali, 2009). MW and IR sounders have the most impact on forecast skills in all satellite observations (Garand et al, 2013;Joo et al, 2013;Cucurull et al, 2014). McNally et al (2014) found that the polar-orbiting satellite data play an important role in decreasing the time and location errors of Hurricane Sandy's track forecasts.…”
Section: Introductionmentioning
confidence: 99%